2020
DOI: 10.1111/cas.14534
|View full text |Cite
|
Sign up to set email alerts
|

FBXO22, an epigenetic multiplayer coordinating senescence, hormone signaling, and metastasis

Abstract: Ubiquitin‐dependent protein degradation has been implicated in the control of various cellular processes such as cell cycle control, transcriptional regulation, DNA damage repair, and apoptosis, many of which are involved in the initiation, progression, metastasis, and drug resistance of cancers. E3 ubiquitin ligases are known to be the second most prevalent cancer‐related functional gene family next to protein kinases. Of these, FBXO22, an F‐box receptor subunit of SCF E3 ligase, has recently been proposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Similarly, a prior study showed that low Fbxo22 expression shared correlation with worse survival in human breast cancer, and knockdown of Fbxo22 promoted breast cancer cell invasiveness (Bai et al 2019 ). Furthermore, Fbxo22 is an epigenetic multiplayer with its strikingly crucial role unveiled in cancer development and therapeutics (Johmura et al 2020 ). Specifically, targeting Fbxo22 can be taken as a promising strategy for cancer therapy, since the inhibitory role of Fbxo22 has been proved in different malignancies, including breast cancer (Cheng et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a prior study showed that low Fbxo22 expression shared correlation with worse survival in human breast cancer, and knockdown of Fbxo22 promoted breast cancer cell invasiveness (Bai et al 2019 ). Furthermore, Fbxo22 is an epigenetic multiplayer with its strikingly crucial role unveiled in cancer development and therapeutics (Johmura et al 2020 ). Specifically, targeting Fbxo22 can be taken as a promising strategy for cancer therapy, since the inhibitory role of Fbxo22 has been proved in different malignancies, including breast cancer (Cheng et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fbxo22 also exerts inhibitory function in breast cancer cell migration and invasion by ubiquitinating SNAIL levels (Sun et al 2018 ). More importantly, the critical role of ubiquitin-dependent protein degradation in various cellular processes has been highlighted, such as cell cycle, transcriptional regulation, DNA damage repair, and apoptosis, and Fbxo22, as an ubiquitin ligase, can be implicated in modulation of the DNA damage repair process (Johmura et al 2020 ). KDM5A (also called JARID1A or RBP2) shows correlation with diverse human cancers, including tumors of the breast and lung (Blair et al 2011 ; Teng et al 2013 , Yang et al 2019 , 2021a , b ].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the ubiquitination system and mitosis is carried out by the protein ubiquitin-conjugating enzyme Cdc34, which participates in the degradation of the protein kinase Wee1-a key negative regulator of mitosis, and this proteolysis event is required for a timely entrance into mitosis [62]. Among participants in ubiquitin-mediated protein degradation, common for morula and blastocyst stages, RNF114 (Ring finger 114) protein was identified as a key molecule for clearance of maternal factors to support maternal-to-zygotic transition and subsequent zygotic genome activation [35]; FBXO22, an F-box receptor subunit of SCF E3 ligase, is a key regulator of cell growth, cell cycle, and cell migration through ubiquitylation of CD147, PTEN, p21, LKB1, KLF4, Bach1, Snail, and HDM2 [63]; the ubiquitin ligase Ltn1, the major component of the ribosome-associated protein quality control system, detects and eliminates aberrant polypeptides through their ubiquitination and degradation by the proteasome [64]; and TRAIP, a ubiquitously expressed nucleolar E3 ubiquitin ligase, is crucial in accurate chromosome segregation during mitosis [65].…”
Section: Discussionmentioning
confidence: 99%
“…F-box-only protein 22 (FBXO22) is an important component of the SKP1-Cullin-F-box (SCF) E3 ubiquitin ligase. FBXO22 participates in multiple biological processes, such as cellular senescence, cell cycle regulation, and autophagy, by recognizing and targeting different substrate molecules [ 9 ]. Several studies have shown that FBXO22 is associated with tumor development and therapeutic response.…”
Section: Introductionmentioning
confidence: 99%